Statistical Geography: Problems in Analyzing Areal Data. - Anderson, Theodore R. (American Sociological Review)
Reviews the book "Statistical Geography: Problems in Analyzing Areal Data," by Otis Dudley Duncan, Ray P. Cuzzort, and Beverly Duncan.